2013
DOI: 10.1093/ageing/afs187
|View full text |Cite
|
Sign up to set email alerts
|

Functional assessments utilised in emergency departments: a systematic review

Abstract: the ISAR or TRST are suitable for fast screening, whereas the OARS or FSAS-ED are more suitable for a comprehensive understanding of functional performance. Further research is warranted and recommendations for ED assessment may change as more becomes known about psychometric properties and clinical applications of other assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 25 publications
0
23
0
6
Order By: Relevance
“…We excluded the Simplified PROFUNCTION index because it has not been evaluated in ED settings. Bissett et al 17 assessed the psychometric properties of the ISAR and TRST, as well as two longer instruments, the Older Adult Resources and Services 96 and the Functional Status Assessment of Seniors in Emergency Departments. 97 They concluded that the shorter instruments were more appropriate for timely screening, whereas the longer instruments provide a more comprehensive understanding of functional performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We excluded the Simplified PROFUNCTION index because it has not been evaluated in ED settings. Bissett et al 17 assessed the psychometric properties of the ISAR and TRST, as well as two longer instruments, the Older Adult Resources and Services 96 and the Functional Status Assessment of Seniors in Emergency Departments. 97 They concluded that the shorter instruments were more appropriate for timely screening, whereas the longer instruments provide a more comprehensive understanding of functional performance.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 This systematic review helps define the accuracy of existing screening tools to identify older ED patients at risk of adverse outcomes. Four recent systematic reviews evaluate the content validity and prognostic accuracy of single geriatric screening instruments such as the Triage Risk Screening Tool (TRST), [15][16][17][18] but none of these systematic reviews evaluates all available instruments or all previously described individual risk factors for post-ED adverse outcomes. The primary objective of this systematic review is to quantify the prognostic accuracy of all individual risk factors and existing instruments for use in ED settings that are designed to identify geriatric adults at increased risk of short-term (1-to 12-month) adverse outcomes following ED visits.…”
mentioning
confidence: 99%
“…Scores were categorised as <10 seconds, 10-19 seconds, 20-29 seconds and ≥30 seconds as originally described by Podsialo [6]. (2) The Older Americans Resources and Service Scale was used to measure functional status, with a decrease of 2/28 points on the Scale defined as functional decline [15][16][17].…”
Section: Study Measuresmentioning
confidence: 99%
“…12 On the other hand, ISAR remains a promising tool for the ED: in a systematic review comparing 15 scales, which incorporated functional related items, ISAR had the best predictive validity and psychometric properties. 18 Recently, the ISAR has been proposed as a screening tool for complex interventions to reduce functional decline after ED visits. 19 The Walter prognostic indicator, on the other hand, showed poorfair predictive values for mortality in hospitalized older adults, 20 but had not been tested in the ED before.…”
Section: Discussionmentioning
confidence: 99%